Plasticity of Performance Curves Can Buffer Reaction Rates from Body Temperature Variation in Active Endotherms - Seebacher, Frank; Little, Alexander G. (Frontiers in Physiology, 2017)
Endotherms regulate their core body temperature by adjusting metabolic heat production and insulation. Endothermic body temperatures are therefore relatively stable compared to external temperatures. The thermal sensitivity of biochemical reaction rates is thought to have co-evolved with body temperature regulation so that optimal reaction rates occur at the regulated body temperature. However, recent data show that core body temperatures even of non-torpid endotherms fluctuate considerably. Additionally, peripheral temperatures can be considerably lower and more variable than core body temperatures. Here we discuss whether published data support the hypothesis that thermal performance curves of physiological reaction rates are plastic so that performance is maintained despite variable body temperatures within active (non-torpid) endotherms, and we explore mechanisms that confer plasticity. There is evidence that thermal performance curves in tissues that experience thermal fluctuations can be plastic, although this question remains relatively unexplored for endotherms. Mechanisms that alter thermal responses locally at the tissue level include transient potential receptor ion channels (TRPV and TRPM) and the AMP-activated protein kinase (AMPK) both of which can influence metabolism and energy expenditure. Additionally, the thermal sensitivity of processes that cause posttranscriptional RNA degradation can promote the relative expression of cold-responsive genes. Endotherms can respond to environmental fluctuations similarly to ectotherms, and thermal plasticity complements core body temperature regulation to increase whole-organism performance. Thermal plasticity is ancestral to endothermic thermoregulation, but it has not lost its selective advantage so that modern endotherms are a physiological composite of ancestral ectothermic and derived endothermic traits.